Implementasi Audit Lingkungan di Kawasan Pesisir Pantai ( Studi Kasus Pantai Di Makassar ) - Tenriwaru Tenriwaru; Popy Alfisyhar (Jurnal Buana Akuntansi, 2023)
Environmental audits can be used to assess how auditing helps manage risks and reduce new obligations. Environmental audit is oriented to managing the environment, which is considered important and successful for the object being measured to improve environmental performance. This research was conducted to find out the efforts made by the government in protecting the environment, especially in the coastal areas of Lae-Lae Island and Tanjung Bayang Beach because environmental audits play an important role in preventing waste pollution and environmental damage due to the low awareness of the local community and local tourists who come to visit the area. this. This study uses primary data obtained directly through direct interviews with the sub-district and coastal communities of Lae-Lae Island and Tanjung Bayang Beach. The data collection method used is qualitative by using a narrative analysis approach. Instruments that support this research are mobile phones, stationery, documentation related to this research locus. The results of this study indicate that environmental audits in the coastal areas of Lae-Lae Island and Tanjung Bayang Beach have never been carried out. In overcoming environmental problems, the government and the community are trying to protect their environment by carrying out community service activities every week and especially on Lae-Lae Island, a government program is being held, namely the procurement of a Tangkasaki boat.